Pengaruh Media Video Animasi Terhadap Hasil Belajar Tematik Siswa SD - Ramdani, Akhmad; Mulyana, Ajeng Tina; Anggraeni, Noerlina; Safaat, Saat; Nurafifah, Sri; Nurjannah, Dian (LPPM Universitas Mohammad Husni Thamrin, 2022)
Learning media is important for learning in elementary schools. This study aims to determine the effect of animated video media on thematic learning outcomes of theme Togetherness class II of Elementary School Based on Islamic religion/ Madrasah Ibtidaiyah (MI) Al-Ikhlas Pondok Gede. This research method uses quantitative research methods, namely Quasi Experiment with Post-test Only Control Design. The sample used is class II which consists of 62 students. Class II A presents 30 students and class II B presents 32 students. The instrument used in the form of a multiple-choice test as many as 40 items that will be tested for validity first. The validity test uses Biseryl Point Correlation, 31 questions are declared valid and 9 questions are declared invalid. The researcher used 30 questions to be used as post-test. Hypothesis testing using ð‘¡ð‘¡ð‘’ð‘ ð‘¡, the results obtained ð‘¡ð‘ð‘œð‘¢ð‘›ð‘¡= 4.674 > 2.000 =ð‘¡ð‘¡ð‘Žð‘ð‘™ð‘’, significance level = 5%. Thus ð»1 is accepted, that there is an influence of animated video media on thematic learning outcomes, theme: togetherness of the 2th graders of Madrasah Ibtidaiyah Al-Ikhlas Pondok Gede